Experimental evaluation of out-of-plane strength of masonry walls retrofitted with oriented strand board - Iuorio, Ornella (2021)
Structural retrofitting is carried out as an economical alternative to demolishing and rebuilding existing masonry structures. Retrofitting is provided to offer structural upgrade and damage-control. This paper presents the application of oriented strand board type 3 (OSB/3) for retrofitting unreinforced masonry walls. Out-of-plane bending test in form of four-point loading was performed on six masonry walls. The test results show that OSB/3 can considerably increase the load and flexure capacity by (1.4 & 1.8), limiting-toughness by (1.6 & 2.4) and overall-toughness by (16 & 10) times compared to plain wall subjected to out-of-plane loading for (single & double-sided) application respectively.